2013 Curriculum Report Application Development at SMK DIAN Indonesia: Pengembangan Aplikasi Raport Kurikulum 2013 Di SMK DIAN Indonesia - Asy’Ari, Mochammad Hasyim; Untari, Rahmania Sri; Hasanah, Fitria Nur (Indonesian Journal of Education Methods Development, 2018)
In SMA Dian Indonesia the report card data entry process is still constrained by the complexity of the application flow that is used. Each subject teacher gives a grade to the homeroom teacher to be processed into a report card. This made it difficult for the homeroom teacher to process the data provided by the subject teacher so that the process of processing report cards was hampered."This study aims to determine the process of developing the 2013 Curriculum Report Card Processing Application at Dian Indonesia High School. Based on the results of the analysis, it was obtained 90% in the very feasible category by media experts, and from the teacher the average validity was obtained 80.7% with the feasible category. So it can be concluded that the development of the 2013 Curriculum Report Card Processing Application is very suitable for use at Dian Indonesia High School.